THE EFFECT OF PRODUCT QUALITY, PRICE, PRICE INNOVATION ON THE PURCHASE INTENTION OF LOWFAT MILK PUDDING - Sinaya, Michael; Dewi, Liliana (International Journal of Application on Economics and Business, 2025)
The purpose of this study was to determine the effect of product quality, price, and product innovation on the purchase interest of low-fat milk pudding in East Surabaya. The sample was selected using purposive sampling technique. Validity and reliability tests were carried out as instrument tests. Data analysis was carried out using multiple linear regression to assess the effect of these variables on purchase interest. Product quality, price, and product innovation were found to have a positive effect on purchase interest of low-fat milk pudding, both individually and simultaneously.